Pencegahan Perilaku Boros sebagai Self Healing dalam Penggunaan Online Shopping: Studi Takhrij dan Syarah Hadis - Yabqiah Rahmi (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
This study aims to analyze the hadith about the prevention of wasteful behavior as self-healing. This study uses a qualitative approach that emphasizes literature study through the takhrij and syarah hadith methods with contemporary analysis. The results of the research and discussion show that the hadith regarding the prevention of wasteful behavior as self-healing has authentic quality so that it can be practiced and used as an argument. The explanation of this hadith shows that giving, tithing and shadaqah are behaviors to prevent waste and for self-healing by means of shopping are allowed but must be in accordance with the budget and limitations. The conclusion of this study is that self-healing through shopping is not something that is prohibited but must be accompanied by giving infaq, giving charity, and tithing because in our assets there are other people's rights; namely the poor, relatives in need, and Ibn Sabil who ran out of provisions.